Problem of juridical evaluation of MGB agents combatant - Samulevičius, Saulius (Genocidas ir rezistencija, 2004)
This article focuses on the coordinated efforts of various authorities to investigate the cases of agents–hitmen, the difficulties encountered, and the ways of serving justice.